Gender differences in professional social responsibility: Are women more responsible at work than men? - Reig-Aleixandre, Natalia; García-Ramos, José Manuel; De la Calle-Maldonado, Carmen (Frontiers in Psychology, 2023)
There is overwhelming evidence that companies with women on their boards of directors have higher levels of Corporate Social Responsibility. The relation between professional women and collective or organisational responsibility has been widely studied. However, to date there has been little research into the individual attitudes of women towards social responsibility. The purpose of this study is to analyse the differences in attitudes towards social responsibility between men and women in their professional life. A study sample (N = 524; 347 women; Medad = 37) was assembled using the LinkedIn social media platform and participants, after providing their informed consent, were asked to answer the Professional Social Responsibility Questionnaire. The results showed significant differences in Professional Social Responsibility between men and women, with moderate effect (t (522) = 2.078; p = .038; η² = .191), in favour of women. The women participants scored higher in the dimensions Discovery of Personal Values (t (522) = 2.342; p = .020; η² = .216) and Social Awareness (t (522) = 2.179; p = .030; η² = .201), both with representative effect sizes. These results suggest that the greater commitment to Corporate Social Responsibility of companies with women on their boards of directors is due, in part, to the greater individual or personal social responsibility of women. Higher levels of Discovery of Personal Values and Social Awareness among women may also result in better decision-making, ultimately accruing to the benefit of the company in terms of its financial results and reputation.